Rapid Detection based Prevalence of Canine Corona Virus (CCoV) and Canine Parvo Virus (CPV) Infection in Diarrheic Dogs in South Gujarat - Desai, Dhruv; Kalyani, Irshadullahkhan; Patel, Dharmesh; Solanki, Jayesh; Vala, Jignesh (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The study was done on detection and prevalence of canine coronavirus (CCoV) and canine parvovirus (CPV) from the diarrhoeic dogs. Dogs presented with the diarrhoea and symptomatic illness, were tested for the CCoV and CPV infection. Diarrhoeic samples were directly processed for rapid diagnostic test using Immuno-chromatography based lateral flow assay test (LFA). It is a fast, rapid and specific for the CCoV and CPV detection. Out of total 109 samples processed by the LFA, 05 (4.58 %) were found positive for CCoV and 37 (33.94%) were positive for CPV. None of the samples showed concomitant infection of both the viruses. Age-wise prevalence of CCoV was found to be 7.93 (5/63) % in ≤3 months age group, and no positive case was found in other age groups. Similarly, the age wise prevalence of CPV was found to be 41.26 (26/63), 25.00 (9/26) and 20.00 (2/10) % in ≤3 months, 3 to 6 months and 6 to 12 months of age group, respectively. The prevalence of CCoV and CPV was found more in young puppies.